Pemanfaatan Pekarangan Untuk Budidaya Tanaman Obat Keluarga di Kelurahan Pati Kidul Kabupaten Pati Jawa Tengah - Shodiq Eko Ariyanto; Nindya Arini; Heny Alpandari (Muria Jurnal Layanan Masyarakat, 2022)
During a pandemic like today, it takes a lot of effort so that the body can avoid the virus. One of the efforts made by the community is consuming processed medicinal plants. The results of the study stated that as many as 48% of people felt it was very relevant to consume herbal medicine. Family medicinal plants (TOGA) are one of the ingredients for making herbal medicine and can be cultivated by every resident of Pati Kidul. The purpose of this community service is to convey information about technology for growing medicinal plants in the yard through lectures, discussions, and direct practical demonstrations. Evaluation of the increase in participants' knowledge was carried out by pre and post-test after socialization and cultivation practice were carried out. Skill evaluation is carried out during a demonstration of direct practice of TOGA cultivation in the yard. The results of the activity showed an increase in knowledge and awareness in utilizing the yard for the cultivation of family medicinal plants. Public knowledge has increased public knowledge by about sixty percent. The results of the cultivation of family medicinal plants can be used as education for family members to be consumed as an action to maintain a healthy body.